2010
DOI: 10.1063/1.3280048
|View full text |Cite
|
Sign up to set email alerts
|

Low hole effective mass in thin InAs nanowires

Abstract: The efficiency of nanoscale electronic devices usually is limited by the decrease in the carrier mobilities when the dimensionality is reduced. Using first principles calculations our results reveal that the hole effective masses of InAs nanowires decrease significantly below a threshold diameter. The mobilities have been estimated, and it is shown that for an optimal range of diameters, the hole mobilities exceeds the bulk value by up to five times, whereas the electron mobilities remain comparable to the bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The band structure for the wurtzite nanowires by passivation dangling bonds are plotted by dos Santos et al 24 and their results show that for all NWs the VBM and VBM-1 are nondegenerate and have low energy dispersion, so we could see the effect of passivation in band structure. The NWs have one type of dangling bond, shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The band structure for the wurtzite nanowires by passivation dangling bonds are plotted by dos Santos et al 24 and their results show that for all NWs the VBM and VBM-1 are nondegenerate and have low energy dispersion, so we could see the effect of passivation in band structure. The NWs have one type of dangling bond, shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…For example, the valence charges for pseudo‐H atoms bonded to In (As) atoms should be $ Z = 1.25$ $ (Z = 0.75),$ instead of $ Z = 1.0$ for real H atoms. Figure 8 shows the representative transversal cross‐sections of the NWs studied in 98. Interestingly, in this study it has been shown that the valence band maximum (VBM) is a nondegenerate level with a high energy dispersion, while the level immediately below in energy (VBM‐1) is two‐fold‐degenerate and has a low energy dispersion.…”
Section: Crystal and Electronic Structure Of Nanowiresmentioning
confidence: 85%
“…The results obtained in Ref. 98 suggest that in extremely thin (2–4 nm diameter) InAs NWs, due to quantum confinement and low effective mass hole states, there is a possibility to obtain p‐type conductance with very high mobility.…”
Section: Crystal and Electronic Structure Of Nanowiresmentioning
confidence: 99%
See 1 more Smart Citation
“…These obtained results are compared with experimental results, which are transferred from the voltage coordinates into the electric field intensity coordinates, reported in literatures to show the validity of the proposed model. In our calculations, the drift velocity of electrons within 10 5 À 1.8 Â 10 6 m/s [25] is supposed as the constant 8 Â 10 5 m/s, the parameter m b is chosen as 0.34 m e [26], the other structure parameters from the GaAs or InGaAs QDIP devices [19,20,27,28] are displayed in Table 1 and are adjusted to the same values as those of the QDIP devices used for the experimental verification. Fig.…”
Section: Detectivitymentioning
confidence: 99%